FORMATION OF PRACTICAL CLASSES ON INFORMATION TECHNOLOGIES IN HIGHER EDUCATIONAL INSTITUTIONS - Suyarov Akram Musayevich (Web of Journals Publishing, 2024)
Nowadays, information technologies provides a clear and easy-to-perform practical task that helps students to form existing knowledge and skills, to use interesting schemes, diagrams, various charts and tables to help them understand it in practical assignments. special attention, etc. are often used. The article provided ample opportunities for students to master many basic concepts relatively easily, conveniently, and robustly. An important factor in this regard is the creation of methodological guidelines, methodological guidelines for the organization of practical training in higher education and their application in the educational process.
Keywords: Higher education, information and communication competence, information culture, professional competencies, key factors of information and communication competence, teaching technologies, the effectiveness of the use of modern teaching technologies for the formation of information and communication competence of teachers.